Removal of Fluoride Ions by Adsorption onto Fe2O3 /Areca Nut Activated Carbon Composite - Joshi, Sahira; Adhikari Pradhananga, Mandira (Journal of the Institute of Engineering, 2017)
The possibility of Fe2O3/Areca nut activated carbon composite as an adsorbent for removal of fluoride from water is presented. Activated carbon (AC) was prepared from Areca nut by chemical activation with phosphoric acid at 400°C under nitrogen atmosphere. The resultant AC was characterized by adsorption of methylene blue and iodine. As indicated by iodine and methylene blue adsorption, the AC was highly micro and meso porous in nature. The adsorbent was prepared by compositing the AC with ferric oxide. Batch adsorption experiments were conducted to describe the effect of pH, contact time and adsorbent dose on fluoride removal from water. Percentage removal of fluoride by the adsorbent was ~75 % at contact time of 180 minutes. The maximum adsorption of fluoride was observed at pH 2 with adsorbent dose of 20 gm/L. The adsorption equilibrium data was analyzed by Langmuir and Freundlich adsorption isotherms. The adsorption data was fitted Langmuir better than Freundlich isotherm. The adsorption capacity of the Fe2O3/Areca nut activated carbon composite was found to be 4.8 mg/gm. The composite adsorbent prepared from Areca nut AC could be an efficient adsorbent for removal of fluoride from water. Journal of the Institute of Engineering, 2016, 12(1): 175-183